2022
DOI: 10.1590/0102-672020210002e1659
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation Attenuates Binge Eating and Food Addiction 1 Year After Roux-en-Y Gastric Bypass: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: BACKGROUND: The use of probiotics as adjuvants in the treatment of eating disorders, known as psychobiotics, has already been investigated as a means of modulating the microbiota-gut-brain axis. AIM: This study aimed to assess the effect of probiotic supplementation on binge eating and food addiction in subjects after Roux-en-Y gastric bypass surgery. METHODS: This is a randomized, double-blind, placebo-controlled trial involving 101 patients who received probiotic (Lactobacillus acidophilus NCFM and Bifid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Meta-analysis indicated that dietary energy, protein, carbohydrate and fiber were statistically reduced in the probiotics group compared to the placebo group. In Calos ’s study, they confirmed that the BES and YFAS statistically reduced in experiment group contrasting to the placebo group [ 26 ]. The probiotics type all included Lactobacillus and Bifidobacterium .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Meta-analysis indicated that dietary energy, protein, carbohydrate and fiber were statistically reduced in the probiotics group compared to the placebo group. In Calos ’s study, they confirmed that the BES and YFAS statistically reduced in experiment group contrasting to the placebo group [ 26 ]. The probiotics type all included Lactobacillus and Bifidobacterium .…”
Section: Discussionmentioning
confidence: 88%
“…6A ). Seven studies assessed data on BMI from baseline postoperatively [ 18 20 , 22 , 24 , 26 , 28 ]. There was a significant difference between both groups (191 vs 187, MD = −2.89 kg/m²; 95% CI [−0.32, 6.09], p = 0.08), with a significant heterogeneity (I² = 97%, P < 0.00001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine studies reviewed, five studies that included lifestyle modification,25 medication26 27 or bariatric surgery28 29 were found to improve symptoms of addictive eating 23. Since publication of this review, a further four intervention studies (a behavioural weight loss programme,30 a brief telephone-based cognitive–behavioural therapy intervention,31 a low-carbohydrate dietary programme32 and a probiotic supplement placebo-controlled trial33) have been trialled with improvement in YFAS addictive eating symptomatology immediately following the intervention. To date, most studies have been limited in sample size and therefore have not been powered to detect a change in addictive eating symptoms 23.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, carbohydrate (CHO)-rich drinks given 2–3 hours prior to the anesthesia induction may add beneficial effects for patients. The intake of CHO-rich drinks not only is safe 11 , 32 but also may decrease postoperative insulin resistance 15 and reduce nausea and vomiting 13 , 20 . Thus, it may enhance postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%